G138(P) Estimated annual incidence of childhood burns within the UK (2013–2015). (24th May 2017) - Davies, K; Johnson, EJ; Roberts, Z; Maguire, S; Kemp, AM
Abstract : Aims: Current burns research focuses on Burns Units admissions, thus underestimating a more widespread problem. This study aims to estimate the annual incidence of burns among children and young people (CYP) in the UK (2013–15) encompassing: mortality, Hospital Admissions (HA), Emergency Attendances (EA), and General Practice (GP). Methods: Sources used are shown in Table 1 . Office for National Statistics mid-year population data were used to estimate annual incidence. Table 1 Sources used to estimate childhood burn incidence Results: The majority of cases are aged <five years; 23.6/10, 000 CYP/year GP contacts, 22.7–35.0/10, 000 EAs, with approximately 10% requiring HA, only 1/3 of whom attend Burns Services, and 4/10 million mortality. (Table 2 ) Table 2 Estimated annual UK childhood burn incidence 2013– 2015 Conclusion: Conservative estimates using mixed sources suggest burns result in 1–6 UK child deaths, 6800 hospitalisations, 40 700 EAs, and 28 900 GP contacts annually. Childhood burns are preventable, yet create significant burden on health services. These findings provide a baseline to inform prevention and service provision.